Assessment of the anthelmintic effect of natural plant cysteine proteinases against the gastrointestinal nematode, Heligmosomoides polygyrus, in vitro - Stepek, Gillian; Buttle, David J.; Duce, I.R.; Lowe, Ann; Behnke, Jerzy M. (Cambridge University Press, 2005)
We examined the mechanism of action and compared the anthelmintic efficacy of cysteine proteinases from papaya, pineapple, fig, kiwi fruit and Egyptian milkweed in vitro using the rodent gastrointestinal nematode Heligmosomoides polygyrus. Within a 2 h incubation period, all the cysteine proteinases, with the exception of the kiwi fruit extract, caused marked damage to the cuticle of H. polygyrus adult male and female worms, reflected in the loss of surface cuticular layers. Efficacy was comparable for both sexes of worms, was dependent on the presence of cysteine and was completely inhibited by the cysteine proteinase inhibitor, E-64. LD50 values indicated that the purified proteinases were more efficacious than the proteinases in the crude latex, with purified ficin, papain, chymopapain, Egyptian milkweed latex extract and pineapple fruit extract, containing fruit bromelain, having the most potent effect. The mechanism of action of these plant enzymes (i.e. an attack on the protective cuticle of the worm) suggests that resistance would be slow to develop in the field. The efficacy and mode of action make plant cysteine proteinases potential candidates for a novel class of anthelmintics urgently required for the treatment of humans and domestic livestock.